Distorções e danos causados pela meritocracia na educação: a rede municipal de ensino de Foz do Iguaçu e o IDEB - Benitez, Silvio (2016)
The purpose of this paper is to analyze the distortions or side effects and damage the implementation of meritocracy in public schools in Foz do Iguaçu, from the priority setting in municipal politics for achieving and exceeding the goals established and agreed by the government federal and municipal government to the assessment performed by an indicator called the Basic education Development Index (Ideb).As sources we used official data on school results of the students in the municipal Foz do Iguaçu education obtained the city Department of Education that municipality, as well as the reports resulting from a special committee of Ideb created by the city council. It follows that the bounded distortion and denounced by the analysis of the US Diane Ravitch author was also present in Foz do Iguaçu, indicating that the use of large-scale assessment systems causes similar effects, wherever it is deployed.